2011
DOI: 10.3892/ol.2011.333
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor induces cholangiocarcinoma cell migration via activation of the MEK1/2 pathway

Abstract: Abstract. The purpose of this study was to investigate the roles played by basic fibroblast growth factor (bFGF) in the induction of cholangiocarcinoma cell progression and to identify the signal transduction molecules that are activated by bFGF in cholangiocarcinoma cells. FGF receptor-2 (FGFR2) was shown to be expressed in two cholangiocarcinoma cell lines (RMCCA1 and KKU-100). Samples from RMCCA1 and KKU-100 were assayed for the mRNA. Phosphorylation levels were determined by Western blotting. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…bFGF also has extensive biological activities, which is present in basement membranes, in the subendothelial extracellular matrix of blood vessels in normal tissue and in periodontal ligament ( 24 ). The study showed that bFGF can regulate cell proliferation and differentiation ( 25 , 26 ) and is able to promote angiogenesis ( 27 ) and nerve regeneration ( 28 , 29 ). In an in vitro experiment, bFGF was found to sustain self-renewal ability, while maintaining differentiation potency ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…bFGF also has extensive biological activities, which is present in basement membranes, in the subendothelial extracellular matrix of blood vessels in normal tissue and in periodontal ligament ( 24 ). The study showed that bFGF can regulate cell proliferation and differentiation ( 25 , 26 ) and is able to promote angiogenesis ( 27 ) and nerve regeneration ( 28 , 29 ). In an in vitro experiment, bFGF was found to sustain self-renewal ability, while maintaining differentiation potency ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…CNV-genes CACNA1 and CACNG7, two calcium channel subunits, compound with RAS guanyl nucleotide releasing proteins which are guanyl nucleotide exchange factors that activate Ras and related GTPases such as RAP [46] . CNV-genes FGFR2 could induce cholangiocarcinoma cell migration via activation of the MEK1/2 pathway [47] . CNV-TF PSG1 regulated upstream activator PTPN7, downstream target ATF2 [48] of MAPK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Data have been accumulated, implicating multiple factors and mechnisms in these processes. Narong and Leelawat 7 observed that by activation of the MEK1/2 pathway, basic fibroblast growth factor induced cholangiocarcinoma cell migration. Overexpression of extracellular matrix protein-1 (ECM1), nuclear protein-1 (NUPR1) and arsenate resistance protein 2 was associated with proliferation and motility of cholangiocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%